Promising strategies to enhance the sustainability of community seed banks - Vernooy, Ronnie; Adokorach, Joyce; Gupta, Arnab; Otieno, Gloria; Rana, Jai; Shrestha, Pitambar; Subedi, Abishkar (MDPI, 2024)
Community seed banks are farmer-managed organizations that conserve and sustainably manage local crop and tree diversity. They are found in many countries of the Global South and increasingly in the Global North. Altogether, they maintain hundreds of crop and tree species and thousands of mostly local varieties and distribute tons of quality seed per year. Through their activities, they share and safeguard the world’s agrobiodiversity, contribute to seed security, and allow farming households in local communities to produce and consume more affordable, secure, diverse, and nutritious foods. However, community seed banks are knowledge-, resource-, and time-intensive organizations that operate through their members’ voluntary contributions. The purpose of this article is to analyze the sustainability challenge of community seed banks and identify strategies that address it. Focus group discussions and key informant interviews were used, complemented by secondary data analysis of research reports and other deliverables, resulting in five case study countries in Africa and Asia. Five promising sustainability strategies can support viable community seed bank development: value addition; nature-positive agriculture; enabling environment and national genebank partnership; networking and digitalization; and modern, low-cost seed quality technologies. Sustainable community seed banks can make important contributions to national seed sector development but they need stronger policy and legal support to maintain their sustainability.